If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-3)=2x+44
We move all terms to the left:
5(x-3)-(2x+44)=0
We multiply parentheses
5x-(2x+44)-15=0
We get rid of parentheses
5x-2x-44-15=0
We add all the numbers together, and all the variables
3x-59=0
We move all terms containing x to the left, all other terms to the right
3x=59
x=59/3
x=19+2/3
| Y=-5x+12(0,-4) | | 7×+1=15x+36 | | 5x-17.50=50 | | 1.3÷x=1 | | x=2.5+0.25x | | 30+0.25x=30.25 | | 16+2.5t=15+0.25t | | x^2-69x+270=0 | | 2y=5y+21 | | 2xN=14 | | 8=x-5÷7 | | x÷0.9=10 | | 42*x=731 | | -3=2+a/12 | | -1+4x=5(1+x) | | Y=9.3x | | F(14)=7x-15 | | 4(x-6)=-(2-6x) | | 42/731=x | | x*42=731 | | Mx8=48 | | n/8+5=11 | | -16-5v+v=7v+5v | | ⅓x-7=15 | | h,15=16,3 | | -1/2=-15/18h | | 4(x-3)=3(x+3)=3x-1 | | x^+10x+45=0 | | ¼x=-2 | | 4/k-5=6/7 | | t+7=-6-3 | | 3(2-x)-(x+2)=55+9(x-3) |